Bending Nanofibers into Nanospirals: Coordination Chemistry as a Tool for Shaping Hydrophobic Assemblies. Issue 1 (13th November 2014) - Kossoy, Elizaveta; Weissman, Haim; Rybtchinski, Boris
Abstract In the current work, we demonstrate how coordination chemistry can be employed to direct self‐assembly based on strong hydrophobic interactions. To investigate the influence of coordination sphere geometry on aqueous self‐assembly, we synthesized complexes of the amphiphilic perylene diimide terpyridine ligand with the first‐row transition‐metal centers (zinc, cobalt, and nickel). In aqueous medium, aggregation of these complexes is induced by hydrophobic interactions between the ligands. However, the final shapes of the resulting assemblies depend on the preferred geometry of the coordination spheres typical for the particular metal center. The self‐assembly process was characterized by UV/Vis spectroscopy, zeta potential measurements, and cryogenic transmission electron microscopy (cryo‐TEM). Coordination of zinc(II) and cobalt(II) leads to the formation of unique nanospiral assemblies, whereas complexation of nickel(II) leads to the formation of straight nanofibers. Notably, coordination bonds are utilized not as connectors between elementary building blocks, but as directing interactions, enabling control over supramolecular geometry.